HUBUNGAN ANTARA KONSEP DIRI AKADEMIK, EFIKASI DIRI AKADEMIK, HARGA DIRI DAN PROKRASTINASI AKADEMIK PADA SISWA SMP NEGERI DI KOTA MALANG - Khotimah, Rahmawati Husnul; Radjah, Carolina Ligya; Handarini, Dany Moenindyah (Jurnal Kajian Bimbingan dan Konseling, 2016)
This study aims to determine the relationship between academic self-concept, academic self-efficacy, self-esteem and academic procrastination. To achieve these goals, used a correlational study design. The population used in the study are students of Junior High School in Malang, the sample totaled 393 students obtained through a multistage random sampling method of sampling. To measure academic self-concept, academic self-efficacy, self-esteem and academic procrastination, use a scale of academic self-concept, academic self-efficacy scale, the scale of self-esteem and academic procrastination scale that has been tested for validity and reliability. The results showed that each variable that academic self-concept, academic self-efficacy and self-esteem negatively related to academic procrastination and together these three variables affect the academic procrastination.